Potensi Sirop Umbi Yakon sebagai Prebiotik Dadih Susu Sapi untuk Asupan DMT2 - Fadila, Dera Nurul; Nasrulloh, Nanang (Poltekkes Kemenkes Yogyakarta, 2023)
Background: The prevalence of people with Type 2 Diabetes Mellitus (T2DM) is ≥90% of the total diabetics worldwide. The formulation of dadih of cow’s milk with the addition of yacon tuber syrup can potentially be a synbiotic product. Consumption of synbiotic products in people with T2DM can provide a glycemic control effect. Objective: Analyzed the effect of adding yacon tuber syrup on total lactic acid bacteria (LAB), pH, total acid, and acceptability of cow’s milk dadih. Method: The research design was experimental with a single-factor completely randomized design (CRD) and three repetitions. The method used to analyze the total LAB test uses total plate count (TPC), the pH test using a pH meter, the total acid test using the acid-base titration method, and the acceptability test using an organoleptic test with a hedonic scale (1-9). Results: the addition of yacon tuber syrup affected the pH value (p= 0,016). While, it did not show a significant effect (p>0,05) between the addition of yacon tuber syrup on total LAB, total acid, and organoleptic. Conclusion: Product F2 with added 20% yacon tuber syrup was the best formula with the highest total LAB and acceptability.